2019
DOI: 10.20524/aog.2019.0376
|View full text |Cite
|
Sign up to set email alerts
|

Multiple plastic versus fully covered metal stents for managing post-liver transplantation anastomotic biliary strictures: a metaanalysis of randomized controlled trials

Abstract: Background Anastomotic biliary strictures (ABS) following liver transplantation (LT) are one of the most common complications, occurring in 4.5-32% of patients. Multiple plastic stenting (MPS) requires multiple sessions, with the associated risk, cost and patient discomfort. Fully covered self-expandable metal stents (FC-SEMS) have increasingly been used in this setting. We performed a systematic review and meta-analysis of randomized controlled trials (RCTs), comparing the role of FC-SEMS and MPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…This was reinforced by a recently published meta-analysis of these studies. 10 This meta-analysis showed a trend toward a higher rate of stricture recurrence among patients who received a cSEMS, which did not reach statistical significance. Adverse events were similar between the 2 groups, including the rate of stent migration (which was approximately 23% among patients treated with cSEMSs) and acute pancreatitis (as long as a biliary sphincterotomy was performed).…”
mentioning
confidence: 73%
“…This was reinforced by a recently published meta-analysis of these studies. 10 This meta-analysis showed a trend toward a higher rate of stricture recurrence among patients who received a cSEMS, which did not reach statistical significance. Adverse events were similar between the 2 groups, including the rate of stent migration (which was approximately 23% among patients treated with cSEMSs) and acute pancreatitis (as long as a biliary sphincterotomy was performed).…”
mentioning
confidence: 73%
“…8 Although FCSEMSs has the advantage of fewer anticipated stent exchanges, a 2013 systematic review 9 and two 2017 meta-analyses 10,11 of observational data did not suggest a clear overall advantage of SEMS use over MPSs for biliary anastomotic stricture after OLT. A 2019 meta-analysis 12 including 4 RCTs concluded that FCSEMSs and MPSs had equal anastomotic biliary stricture resolution and recurrence and similar overall rates of adverse events or stent migration. A trend towards a higher stricture recurrence rate in FCSEMS disappeared when trials with shorter stent indwell time were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analyses [22,23] found SEMS and MPS had equal ABS resolution and recurrence (odds ratio 1.05, 95% confidence interval 0.43-2.56), although there was a trend towards a higher recurrence rate in SEMS. This greater stricture recurrence rate was no longer significant when trials with a shorter stent indwelling time were excluded [22], with benefits for 6 months compared to 3 months [24,25]. ESGE guidelines recommend temporary insertion of MPS for the treatment of benign ABS following orthotopic liver transplantation pending further evidence about SEMS (weak recommendation, moderate-quality evidence) [5].…”
Section: Type 2 Stricturesmentioning
confidence: 97%
“…Post-liver transplant, strictures can be anastomotic biliary strictures (ABSs) or non-anastomotic biliary strictures. For anastomotic biliary strictures, MPS is the gold standard [22]. Meta-analyses [22,23] found SEMS and MPS had equal ABS resolution and recurrence (odds ratio 1.05, 95% confidence interval 0.43-2.56), although there was a trend towards a higher recurrence rate in SEMS.…”
Section: Type 2 Stricturesmentioning
confidence: 99%
See 1 more Smart Citation